Disentangling the function and structural modularity of the membrane arm from respiratory complex I - Castro, Paulo (2022)
Life depends on a great variety of energy transducing enzymes that establish and maintain a transmembrane difference of electrochemical potential. In this thesis, the presence of the different respiratory enzyme complexes in the several phyla of life was studied. The results highlight the remarkable diversity and modularity of respiratory chains, allowing the existence of life in a great array of environments. (...)